Me (Moth) - McBride, Amber (Feiwel and Friends, 2021)
Debut YA novel-in-verse by Amber McBride about Moth, who lost her family in an accident, and Sani, who is battling ongoing depression, take a road trip that has them chasing ghosts and searching for ancestors, which helps them move forward in surprising, powerful and unforgettable ways.